Minimal secularism: lessons for, and from, India - Laborde, C (Cambridge University Press, 2020)
Does liberal democracy require a strict separation between state and religion? In Anglophone liberal political theory, the separationist model of the First Amendment of the US Constitution has provided the basic template for the rightful relationship between state and religion. Yet this model is ill suited to the evaluation of the secular achievements of most states, including India. This Article sets out a new framework, minimal secularism, as a transnational framework of normative comparison. Minimal secularism does not single out religion as special; and it appeals to abstract liberal democratic ideals such as equal inclusion and personal liberty. Actual debates about secularism in India are shown to revolve around these ideals. The study of recent Indian controversies - about the Uniform Civil Code, the status of Muslims and the rise of BJP nationalism - also sheds light on some blind spots of western secularism and the conception of sovereignty and religion it relies on.